Macroepiphyte biodiversity on Kappaphycus alvarezii surface and its interaction with environment in cultivation centers on Lombok Island, Indonesia - MURSAL GHAZALI; WAHYU WIDORETNO; ESTRI LARAS ARUMINGTYAS; CATUR RETNANINGDYAH (Society for Indonesian Biodiversity, 2022)
Abstract. Ghazali M, Widoretno W, Arumingtyas EL, Retnaningdyah C. 2022. Macroepiphyte biodiversity on Kappaphycus alvarezii surface and its interaction with environment in cultivation centers on Lombok Island, Indonesia. Biodiversitas 23: 6284-6292. The aims of this paper are to investigate the influence of environmental factors on the diversity of macroepiphytes in Kappaphycus alvarezii. Macroepiphyte sampling was carried out at four cultivation centers: Seriwe Bay, Ekas Bay, Gerupuk Bay, and Siwak of Lombok Island, West Nusa Tenggara, Indonesia. Several stations were placed at each location, and at each station were used one to three cultivation units with five replications. Environmental data measurements were carried out at the time of sampling. Some parameters were measured: pH, temperature, salinity, current velocity, brightness, DO, BOD, nitrate, phosphate, and TSS. Data analysis was performed using several diversity indices. In addition, a biplot analysis was performed using PCA to analyze the correlation between environmental factors and environmental factors to macroepiphytes. The results showed that the most dominant species was Polysiphonia spaerocharpa, and the second was Ceramium sp1. The highest richness and abundance were found in Ekas Bay. The highest species dominance was in Siwak. The highest diversity index was in Ekas Bay. The correlation between environmental factors showed that hemeroby harmed depth, phosphate, and DO and positively affected BOD and the thallus surface structure. The principal correlation analysis showed that the abundance of macroepiphyte was influenced by BOD, the roughness of host thallus, and the hemeroby index.